2020
DOI: 10.2217/rme-2020-0032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicotine on the Translation of Stem Cell Therapy

Abstract: Although stem cell therapy has tremendous therapeutic potential, clinical translation of stem cell therapy has yet to be fully realized. Recently, patient comorbidities and lifestyle choices have emerged to be important factors in the efficacy of stem cell therapy. Tobacco usage is an important risk factor for numerous diseases, and nicotine exposure specifically has become increasing more prevalent with the rising use of electronic cigarettes. This review describes the effects of nicotine exposure on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Indeed, the selective α7 nAChR agonist ICH3, was shown to enhance MSCs migration [70]. Likewise, α-BTX, the α7 nAChR selective antagonist had the ability to block the detrimental effects of nicotine in several MSCs [67,71,72]. These data display an interesting potential for targeting ion channels that influence MSC function.…”
Section: Achrs As a Potential Target To Regulate Mscs Functionmentioning
confidence: 90%
See 1 more Smart Citation
“…Indeed, the selective α7 nAChR agonist ICH3, was shown to enhance MSCs migration [70]. Likewise, α-BTX, the α7 nAChR selective antagonist had the ability to block the detrimental effects of nicotine in several MSCs [67,71,72]. These data display an interesting potential for targeting ion channels that influence MSC function.…”
Section: Achrs As a Potential Target To Regulate Mscs Functionmentioning
confidence: 90%
“…The study also provides in vivo data demonstrating impaired migration of transplanted hMSCs to the bone marrow and spleen in mice as a result of nicotine exposure. Indeed, in a separate study, it has been suggested that higher doses of nicotine cause apoptosis and impair proliferation, while at non-toxic concentrations it decreases the migratory potential of MSCs [67].…”
Section: Expression Of Nachrs In Mscs Bone Marrow Mscs (Bm-mscs)mentioning
confidence: 99%
“…Smoker-derived MSCs generated significantly less bone matrix in comparison to cells isolated from nonsmokers ( Zhao et al, 2018 ). Upon autologous implantation of these scaffolds, the stability of implants was higher in nonsmokers ( Chan and Huang, 2020 ). Intriguingly, smoker-derived MSCs produced an elevated level of lipid contents even after several weeks of culture in a nicotine-free medium compared with cells isolated from nonsmokers ( Ng et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The growing trend of cardiovascular patients, which has doubled from 1990 to 2019, necessitates urgent action for designing and implementing more efficient therapeutic strategies ( Roth et al, 2020 ). New policies resort to using the potential of stem cells, and thereby, nearly one-fifth of all stem cell-based clinical trials in the new decade of 2020 were designed to be conducted in the area of CVD ( Chan and Huang, 2020 ). Despite promising findings, the clinical translation of stem cell-based therapeutics has not reached a consensus yet.…”
Section: Introductionmentioning
confidence: 99%
“…For example, emerging research in preclinical models suggests that lifestyle choices such as tobacco exposure can negatively affect the efficacy of stem cell therapy for treatment of PAD. 110,111 Therefore, autologous stem cells from some patients may need preconditioning to reverse or reprogram the cells into a functional state before transplantation. In this regard, biomaterials can become a tool to modulate cellular function.…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%